Effectiveness of Thinopyrum ponticum-derived wheat leaf rust resistance gene, Lr24 in India - a revisit - Sivasamy, Murugasamy; Jayaprakash, Paramasivan; Vikas, Venu Kumaran; Bharadwaj, Subhash Chander; C, Manjunatha; Rebekah, Nisha; Paneer, Shajitha; A, Sindhu; Vijaishree, S; Peter, John (Journal of Cereal Research, 2022)
Leaf or brown rust is one of the most devastating rust diseases in wheat. Development and deployment of resistance wheat cultivars is considered as the most effective, economic and sustainable method of protecting against the yield losses due to leaf rust. Though several alien resistance genes have been reported and utilized, Thinopyron ponticum derived leaf rust resistance gene Lr24/Sr24 has been proved to be effective for nearly three decades in India. The effectiveness of this gene was validated recently at seedling and adult plant stage. In the sixteen (16) backcrossed inbred lines (BILs) along with their corresponding recurrent parents showed resistance reaction to the existing pathotypes. Furthermore the presence of Lr24 gene was confirmed in BILs through molecular markers. The results showed that Lr24 gene conferred all stage resistance to the existing pathotypes of P. triticina f.sp. tritici. This emphasizes the importance of Lr24 gene in Indian wheat breeding program and its prolonged protection of wheat crop from leaf rust in India.